Improving the optical and thermoelectric properties of Cs2InAgCl6 with heavy substitutional doping: a DFT insight - Bhamu, K. C.; Haque, Enamul; Praveen, C. S.; Kumar, Nandha; Yumnam, G.; Hossain, Md. Anwar; Sharma, Gautam (RSC Advances, 2021)
The next-generation indium-based lead-free halide material Cs2InAgCl6 is promising for photovoltaic applications due to its good air stability and non-toxic behavior. However, its wide bandgap (>3 eV) is not suitable for the solar spectrum and hence reduces its photoelectronic efficiency for device applications. Here we report a significant bandgap reduction from 2.85 eV to 0.65 eV via substitutional doping and its effects on the optoelectronic and opto-thermoelectric properties from a first-principles study. The results predict that Sn/Pb and Ga and Cu co-doping will enhance the density of states significantly near the valence band maximum (VBM) and thus reduce the bandgap via shifting the VBM upward, while alkali metals (K/Rb) slightly increase the bandgap. A strong absorption peak near the Shockley-Queisser limit is observed in the co-doped case, while in the Sn/Pb-doped case, we notice a peak in the middle of the visible region of the solar spectrum. The nature of the bandgap is indirect with Cu-Ga/Pb/Sn doping, and a significant reduction in the bandgap, from 2.85 eV to 0.65 eV, is observed in the case of Ga-Cu co-doping. We observe a significant increase in the power factor (PF) (2.03 mW m(-1) K-2) for the n-type carrier after Pb-doping, which is similar to 3.5 times higher than in the pristine case (0.6 mW m (-1) K-2) at 500 K.